2015
DOI: 10.1016/j.oooo.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 expression in oral epithelial dysplasia and oral squamous cell carcinoma

Abstract: (144 words)Objective.LGR5 is pivotal to oral cavity development and is implicated in epithelial malignancy whereby stimulation of LGR5 potentiates canonical Wnt signalling. This investigation tested our hypothesis of a correlation between LGR5 expression and the severity of oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC).Study Design.Immunoreactive LGR5 protein expression was quantified in 342 tissue samples ranging in disease severity from normal through mild and moderate/severe OED to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Numerous studies have compared the biological properties of premalignant lesions with their malignant potential; to this end, the expression of some biomarkers in oral precancerous and cancerous lesions have been compared. 6,23,[25][26][27][28] The molecular events that cause a premalignant lesion to turn into a carcinoma are still unknown, and it is still impossible to predict which premalignant lesion will progress to carcinoma. 29 …”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have compared the biological properties of premalignant lesions with their malignant potential; to this end, the expression of some biomarkers in oral precancerous and cancerous lesions have been compared. 6,23,[25][26][27][28] The molecular events that cause a premalignant lesion to turn into a carcinoma are still unknown, and it is still impossible to predict which premalignant lesion will progress to carcinoma. 29 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, only the LGR5Δ5 splice variant but not LGR5FL or LGR5Δ8 mRNA level have a prognostic value for OSCC patients. In contrast another study in OSCC showed that the LGR5 expression increased during the process of the malignant transformation but there was no association between the LGR5 protein expression and other clinical parameters [22]. However, these investigators performed LGR5 immunohistochemistry and therefore a discrimination between splice variant products of LGR5 was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…LGR5 was found to be overexpressed in colorectal cancer [1418] and several studies indicated that LGR5 expression is associated with colorectal carcinogenesis, tumor growth and metastasis [1820]. Subsequent studies demonstrated that LGR5 is expressed by a diverse range of adult tissues and organs and acts as a biomarker for adult stem cells in certain tissues including oral tissues [21, 22]. Furthermore, LGR5 was found to be overexpressed in several carcinomas having a close association with initiation and recurrence of different cancer types and correlating with tumor growth, invasion and poor prognosis [18, 20, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGR5 is the receptor for proteins of the R-spondin family, which synergize with Wnt ligands in the stimulation of the Wnt/β-catenin pathway and play a role in adult stem cell regulation. The expression of LGR5 was increased in oral dysplasia and oral carcinoma [98]. On the other hand, the phenotype of cancer stem-like cells derived from HNSCC patients was associated with c-MET receptor-dependent activation of canonical Wnt signaling.…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 95%